The role of microRNA-325-3p as a critical player in cell death in NSCs and astrocytes - Lee, Yukyeong; Lee, Seung-Won; Jeong, Dahee; Lee, Hye Jeong; Ko, Kinarm (Frontiers in Cell and Developmental Biology, 2024)
Neural stem cells (NSCs) are defined by their ability to self-renew and generate various cell types within the nervous system. Understanding the underlying mechanism by which NSCs proliferate and differentiate is crucial for the efficient modulation of in vivo neurogenesis. MicroRNAs are small non-coding RNAs controlling gene expression concerned in post-transcriptional control by blocking messenger RNA (mRNA) translation or degrading mRNA. MicroRNAs play a role as modulators by matching target mRNAs. Recent studies have discussed the biological mechanism of microRNA regulation in neurogenesis. To investigate the role of microRNAs in NSCs and NSC-derived glial cells, we screened out NSC-specific microRNAs by using miRNome-wide screening. Then, we induced downregulation by the sponge against the specific microRNA to evaluate the functional role of the microRNA in proliferation, differentiation, and apoptosis in NSCs and NSC-derived astrocytes. We found that microRNA-325-3p is highly expressed in NSCs and astrocytes. Furthermore, we showed that microRNA-325-3p is a regulator of apoptosis by targeting brain-specific angiogenesis inhibitor (BAI1), which is a receptor for apoptotic cells and expressed in the brain and cultured astrocytes. Downregulation of microRNA-325-3p using an inducible sponge system induced cell death by regulating BAI1 in NSCs and NSC-derived astrocytes. Overall, our findings can provide an insight into the potential roles of NSC-specific microRNAs in brain neurogenesis and suggest the possible usage of the microRNAs as biomarkers of neurodegenerative disease.